Stories Past Present Class-VIII - (:unkn) unknown (Department of School & Mass Education, Odisha, 2017)
Stories Past Present is a prescribed English textbook for class-8 in Odia medium schools. The book is designed to help the students in learning English language.
Keywords: Odia; Stories Past Present Class-VIII; English Language Learning; Odia; Odia